Case study SapuraCrest Petroleum Berhad importants screening application in the selection process / Nur Farah Umira Mustaqim - Mustaqim, Nur Farah Umira (2010)
This research was carried out to identify the factors that influence customer’s satisfaction towards This study is to examine the important screening application in the selection process in the SapuraCrest Petroleum Berhad. This study aimed to focus on the factors that will affect the successful of negotiation session in SapuraCrest while can reduce the shortage of expatriate in Sapura company. This study will determine the important of screening during the selection. In the other hand, this study will highlight the process that may need some improvement for the screening activity in order to achieve 100 percent successful in selection proceed Based on the all variables, the qualitative study will be done by focusing to the content analysis in order to gather the data. The source of data will focus on the interview and observation which is related to the study. After all data has been gathered, it will be interpreted to make it sense for supporting the problems identified. The findings from this study will provide information that can be use for further investigation in the same nature of study or industry.